Spatial overlay: valuing the existing through juxtaposition - Rohiman, Wazir (School of Architecture, Planning and Geomatics, 2018)
Adaptive reuse can be viewed as a catalytic process that upgrades an existing building into its current temporal reality. This process has given rise to the practice of facadism; a practice that operates in the middle ground between two extreme approaches of either preservation or complete destruction of an existing building. Preservation is concerned primarily with the keeping of the existing building in its intact form, architectural language, tectonic and spatial qualities. New programmes demand new spatial needs, the practice of preservation leaves very little space for major intervention to take place, remaining often unsatisfactory for the new uses of the building. On the other hand, the anti-preservationist's approach leads to total disregard of the existing whereby complete demolition is likely to take place. The practice of facadism locates itself in between these two approaches. While it serves its purpose of upgrading the existing architecture, this paradoxical practice is somewhat more deceptive than pristine preservation or complete demolition. The problematic issue is that it pretends to value and retain part of the building while ignoring the set of values of the whole that the existing building has to offer. More importantly, it erases the spatial and programmatic qualities of the existing while only considering the material and physical connection between the old and the new. ln the majority of cases, this results in a severe dismembering and the gut-removal of the existing building's internal elements. The upgrading of an existing building is bound to exert major changes that entirely transform the building's image. This reality is acknowledged and regarded as unavoidable throughout the dissertation. However, when the whole and the set of values of the existing are ignored, the new intervention creates a totally alien architecture that offer no substance that can relate to the existing building. This dissertation set out to find a dialogue between the old and the new, by respecting the old without compromising on the upgrade. The aim of this dissertation covers the process of space-making that relies primarily on taking the valued elements, whether physical, spatial or programmatic from the existing to drive the design of the new intervention forward. Unlike the practice of facadism, where the process emerges from design intentions that do not value the existing, the process employed in this design dissertation frames the existing building as the starting point of the design process. The new intervention therefore originates from the spatial overlay of the existing building, where the latter becomes the main input of the design process for the former. Since the practice of facadism does not value space, the emphasis for the spatial overlay is to find the right fit between maintaining spatial qualities of the existing while juxtaposing the requirements of the new design intervention.